Ketidakkonsistenan Dampak Merger dan Akuisisi pada Rasio Keuangan: Literature Review Berdasarkan Sektor dan Metode Evaluasi - Tesa Br Simbolon; Adwitia Dian Savitri; Abiem It’sna Muafa; Septi Yulia Ratih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the inconsistency of merger and acquisition (M&A) impacts on financial ratio performance across sectors and evaluation methods. This literature review synthesizes ten empirical studies published between 2022 and 2025, focusing on financial indicators before and after M&A transactions. The findings show that the effect of M&A on financial performance varies widely depending on the industry context, time horizon, and analytical technique used. Studies in the technology and telecommunication sectors demonstrate significant improvements in profitability and operational efficiency, while research involving manufacturing and non-financial firms commonly reports insignificant changes in key ratios such as current ratio, total asset turnover, return on assets, and return on equity. Methodological differences also influence the reported outcomes, where long-term observations and comparative statistical testing tend to reveal a more pronounced financial impact compared to short-term assessment. These results indicate that M&A does not uniformly drive financial improvement and its success depends on post-integration strategy, sector dynamics, and measurement design. This study highlights the necessity of standardized evaluation frameworks to ensure more reliable performance interpretation in future M&A research.